Research Ethics in Social Studies: Indonesian Perspectives - Drajati, Nur Arifah; Trinugraha, Yosafat Hermawan; Sukmawati, Fatma; RAKERDA, HILDA; Ilmi, Ma'rifatul (Universitas Bengkulu, 2023)
The necessary standards for conducting and disseminating research rely on research ethics. Research ethics determine whether research is integrity-based and adequately completed. Given the significant role of ethics in research, much of the research in Indonesia does not fall under the remit of research ethics committees (REC), especially research in studies, such as in education. This condition might happen because of the lack of knowledge about ethics in research and their significance. Thus, this case study aims to observe whether or not Indonesian researchers have enough knowledge about research ethics and their perception of the essential roles of ethics in research. We collected the data through a written interview with 20 participants selected purposely. The results of this study provided an extended discussion of knowledge and understanding of research ethics among Indonesian researchers in the educational field. We concluded that social researchers’ knowledge, support, and access to gain ethical clearance for the research should receive particular attention so that research in social studies could be ethically conducted and presented with qualified and validated results.